Paleoecological inferences for Turborotalita Nikolasi (Koutsoukos, 2014) based on stable carbon and oxygen isotopes - Krahl, Guilherme; Koutsoukos, Eduardo A. M.; Kochhann, Karlos G. D.; Bom, Marlone H. H.; Fauth, Gerson; Esswein, Andressa; Meirelles, Valeska (Journal of foraminiferal research, 2023)
The species Turborotalita nikolasi first appeared immediately after the Cretaceous-Paleogene (K-Pg) boundary and is considered the progenitor of all Cenozoic normal perforate species. We present δ18O and δ13C isotope signals of T. nikolasi specimens and compare them with those of mixed-layer (Guembelina cretacea), thermocline (Subbotina trivialis and Chiloguembelina midwayensis), and deep water (Nuttalides truempyi) species with glassy shell preservation from São Paulo Plateau [Deep Sea Drilling Project (DSDP) Site 356]. Turborotalita nikolasi δ18O values are similar to those of G. cretacea, suggesting that both species cohabited the mixed layer. Values of δ13C for T. nikolasi are higher than those of all other planktic foraminiferal species, which may have been due to the presence of photosymbionts, and thus might represent the earliest known record of photosymbiosis for Cenozoic planktic foraminifera. Nuttalides truempyi δ13C values are remarkably high at Site 356, indicating low 12C abundance in deep waters, which could be related to reduced inefficiency of the biological pump in transporting 12C to the bottom of the ocean after the K-Pg boundary during the first ∼300 kyr of the Danian.
Gesehen am 19.06.2023